INTERVENSI KESEHATAN IBU DAN ANAK MELALUI KOLABORASI PUSKESMAS DAN LEMBAGA MASYARAKAT DAN SWASTA DI KELURAHAN MANGASA KECAMATAN TAMALATE - Iwan, Iwan; Mato, Rusni; Sudirman, Sudirman; Rahman, Rahman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Maternal and Child Health (MCH) is a crucial aspect, yet continues to face significant challenges, reflected in high maternal and infant mortality rates. These issues stem from limited access to quality health services, low awareness of balanced nutrition, exclusive breastfeed ing, and stunting prevention. The situation is worsened by shortages of medical personnel and equipment at the community health center, as well as low community participation in Posyandu and maternal classes. Therefore, a comprehensive interv ention through collaboration among the health center, community organizations (health cadres, PKK, Posyandu), and the private sector through CSR programs is needed. Key efforts include training health cadres for home visits and support to high-risk pregnant women and children; engaging the private sector to provide medical equipment, medicines, and health education; and utilizing digital tools, such as mobile applications, for data collection and service reminders. This collaborative approach is expected to improve service quality and reduce maternal and infant mortality in Mangasa.